2012
DOI: 10.1007/s10457-012-9494-8
|View full text |Cite
|
Sign up to set email alerts
|

Ecological benefits provided by alley cropping systems for production of woody biomass in the temperate region: a review

Abstract: In temperate Europe alley cropping systems which integrate strips of short rotation coppices into conventional agricultural fields (ACS) are receiving increasing attention. These systems can be used for crops and woody biomass production at the same time, enabling farmers to diversify the provision of market goods. Adding trees into the agricultural land creates various additional benefits for the farmer and society, also known as ecosystem services. However, tree-crop interactions in the temperate region have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
122
2
7

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 176 publications
(142 citation statements)
references
References 142 publications
(153 reference statements)
4
122
2
7
Order By: Relevance
“…In a modeling study of the environmental benefits in the Mediterranean and Atlantic regions of Europe, soil erosion and nitrogen leaching were found to be lower than in conventional cropping land, and carbon sequestration was enhanced [157]. In a review of the benefits of alley cropping systems combining agriculture and short rotation coppices by growing trees in agricultural sites in temperate Europe, these systems proved efficient for soil carbon sequestration, improving fertility, controlling erosion, storing water and regulating its quality, and increasing the overall productivity compared to conventional farming [158]. In a review of alley cropping agroforestry systems in Europe, other authors also reported overall increases in the soil organic C stocks [159].…”
Section: Organic Farming Agroecology and Agroforestrymentioning
confidence: 99%
“…In a modeling study of the environmental benefits in the Mediterranean and Atlantic regions of Europe, soil erosion and nitrogen leaching were found to be lower than in conventional cropping land, and carbon sequestration was enhanced [157]. In a review of the benefits of alley cropping systems combining agriculture and short rotation coppices by growing trees in agricultural sites in temperate Europe, these systems proved efficient for soil carbon sequestration, improving fertility, controlling erosion, storing water and regulating its quality, and increasing the overall productivity compared to conventional farming [158]. In a review of alley cropping agroforestry systems in Europe, other authors also reported overall increases in the soil organic C stocks [159].…”
Section: Organic Farming Agroecology and Agroforestrymentioning
confidence: 99%
“…In this context, research on agroforestry systems aims at quantifying and analyzing the spatiotemporal patterns of resource capture between species. However, papers covering temperate agroforestry systems reveal contrasting results (Luedeling et al, 2016;Smith et al, 2013;Tsonkova et al, 2012). This is probably due to the fact that the interactions between two different species may depend on multiple factors such as the design of the mixture (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Meta-analyses from temperate areas present compelling evidence that an increase in the complexity in the agricultural landscape through agroforestry systems delivers more supporting and regulating ecosystem services, such as carbon sequestration, maintenance of biodiversity, water quality, nutrient recycling, soil fertility and erosion, than conventional land use (Tsonkova et al 2012;Kim et al 2016;Torralba et al 2016;Wilson and Lovell 2016).…”
Section: Introductionmentioning
confidence: 99%